2011 Joint Conference of the 21st International Workshop on Software Measurement and the 6th International Conference on Softwa 2011
DOI: 10.1109/iwsm-mensura.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Good or Bad Committers? A Case Study of Committers' Cautiousness and the Consequences on the Bug Fixing Process in the Eclipse Project

Abstract: Abstract-There are many roles to play in the bug fixing process in open source software development. A developer called "Committer", who has a permission to submit a patch into software repository, plays a major role in this process and hold a key to the successfulness of the project. In this work, we have observed each committer activities from the EclipsePlatform bug tracking system and version archives. Despite the importance of committer's activities, we suspected that sometimes committers can make mistake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The transparent nature and social media attached to the project development platforms such as GitHub and SourceForge.NET also led developers to become extremely aware that their contribution actions had an audience and therefore focused on the number of contributions rather than the quality of the contribution. Although these models can help in understanding how a developer is promoted to a committer role, there have been few studies that use survey methods to subjectively measure developer perceptions that influence their contribution behaviour [10,[36][37][38][39]. This suggests the potential use of surveys to understand individual developer involvement with the blockchain project.…”
Section: Committer Assessment Practice Overviewmentioning
confidence: 99%
“…The transparent nature and social media attached to the project development platforms such as GitHub and SourceForge.NET also led developers to become extremely aware that their contribution actions had an audience and therefore focused on the number of contributions rather than the quality of the contribution. Although these models can help in understanding how a developer is promoted to a committer role, there have been few studies that use survey methods to subjectively measure developer perceptions that influence their contribution behaviour [10,[36][37][38][39]. This suggests the potential use of surveys to understand individual developer involvement with the blockchain project.…”
Section: Committer Assessment Practice Overviewmentioning
confidence: 99%
“…Capable people are always the key to the success [32]. However, for largescale projects it is difficult to identify developers with good potential to become committers [31], we therefore proposed an approach to select committers.…”
Section: Selection Of Candidate Committersmentioning
confidence: 99%
“…Jongyindee et al (2011) found that bugs fixed by more experienced developers are less likely to be reopened.…”
Section: Bug Reopeningmentioning
confidence: 99%
“…Regarding the impact of reopened bugs, the literature reports reopening rates as low as 1.4 % (Almossawi 2012) and as high as 11.7 % (Jongyindee et al 2011), obtained from open source projects. Also, reopened bugs are said to have a life cycle from 2 to 5 times higher (Jongyindee et al 2011;Shihab et al 2010) than regular bugs, and to involve the participation of 40 % more developers (Jongyindee et al 2011).…”
Section: Bug Reopeningmentioning
confidence: 99%
See 1 more Smart Citation